Annual Review of Gerontology and Geriatrics 18, 1998 : Focus on Interventions Research with Older Adults. - Schulz, Richard (Springer Pub. Co., 1998)
Focuses on behavioral and pharmacologic interventions for depression, treatments of late-life insomnia, behavior interventions in nursing homes, interventions for incontinence, and home modification interventions. For clinicians and researchers.